(untitled) (REMUNOM, 2023)
Sleep bruxism is a motor action characterized by the act of grinding, grinding or clenching the teeth, through the mandibular muscles. Many causes are correlated to this action, such as psychosocial aspects, exemplificatively stress, anxiety and the use of antidepressant drugs. It is essential to know and predict the relationship between this factor and the possible complications in the procedures in implant dentistry, since bruxism causes excessive load and deterioration and has a high chance of failure in this procedure